UKURAN PERUSAHAAN, LEVERAGE, RISIKO SAHAM DI PERUSAHAAN PERBANKAN - Ariya Parendra; Amrie Firmansyah; Dani Kharismawan Prakosa (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
Stock investment is one of the most attractive forms of investment for investors. Investors can choose various sectors of companies listed on the Indonesia Stock Exchange (IDX) to place their funds in investing in shares. One of the sectors with high capitalization in recent years is the banking sector, where investors have been attracted to buying banking companies' shares. Even so, investors in investing in stocks must pay attention to the factors associated with the risk of investing in stocks, whether it is a total risk or a systematic risk that cannot be prevented by diversification. The purpose of this study is to empirically examine the effect of firm size, leverage, and profitability on stock risk. The sample used in this study is a banking company listed on the Indonesia Stock Exchange (BEI) and has stock beta data released by Pefindo during 2016-2019. Based on purposive sampling, 23 companies were selected so that the total sample is 92 observations. Hypothesis testing is performed using multiple linear regression analysis of panel data. The test results suggest that company size has a positive effect on systematic risk, but it negatively affects the total risk. Leverage is not associated with systematic risk and total risk. Keywords: beta, leverage, banking industry, total risk, firm size